Analisis Kinerja Keuangan dengan Metode Economic Value-Added pada Studi Kasus Perusahaan Subsektor Pertambangan Minyak dan Gas Bumi yang Terdaftar di Indeks Saham Syariah Indonesia (ISSI) - Endah Fatmasari; Bambang Sugeng Dwiyanto (Jurnal Maksipreneur, 2019)
Oil and gas are non-renewable natural resources, whick means they can be exhausted within a certain periode of time, if no new reserves of oil and natural gas resources are found. Energy, especially oil and gas, is very limited amount, but the world’s needs for oil and gas are currently increasing, so making investments in the oil and gas mining subsector will be an attractive choice for investors. World demand of oil and gas increases, while the limited its availability in each country has caused fluctuations in its exports and imports. They face a difficult assessment of the company performance in this subsector. Therefore, we need an analysis of the financial performance in oil and gas mining subsector companies as a tool to assess how the performance of the in this area. Economic value-added (EVA) method is one of the right measurement tools to assess the performance of companies in the mining sector. The aim of this study is to determine the financial performance of companies by using the EVA (economic value-added) method in the oil and gas subsector companies listed on the ISSI (Indonesian Sharia Stock Index) in period 2013-2017. The calculation of EVA value of a company is preceded by determining the value of Net Operating Profit After Tax (NOPAT), Weighted Average Cost of Capital (WACC), capital charges (CC), and invested capital (IC) from data that has been collected in the secondary sources. Four companies in oil and gas mining subsector listed on the Indonesia Sharia Stock Index (ISSI) were analyzed in this research. The results showed that two companies have positive EVA, while rest of two companies have positive and negatif EVA in certain years. A positive EVA means that there is an economic added-value to the company.